2021
DOI: 10.1101/2021.10.23.465040
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Light-independent regulation of algal photoprotection by CO2availability

Abstract: Photosynthetic algae cope with suboptimal levels of light and CO2. In low CO2 and excess light, the green alga Chlamydomonas reinhardtii activates a CO2 Concentrating Mechanism (CCM) and photoprotection; the latter is mediated by LHCSR1/3 and PSBS. How light and CO2 signals converge to regulate photoprotective responses remains unclear. Here we show that excess light activates expression of photoprotective and CCM-related genes and that depletion of CO2 drives these responses, even in total darkness. High CO2 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(28 citation statements)
references
References 90 publications
(186 reference statements)
6
22
0
Order By: Relevance
“…Indeed, we observed that LHCSR3 was still induced by blue light (Supplementary Figure 5) and UV-B radiation (Figure 6) in the cia5 mutant, although both the basal and induced levels of expression were lower than in WT cells (but similar fold-change). The lower LHCSR3 mRNA levels present in dark-acclimated cia5 mutant cells are in line with the work by Ruiz-Sola et al (2021) that demonstrates that CIA5-dependent LHCSR3 induction also occurred in total darkness when the availability of inorganic carbon becomes very low (Figure 6B).…”
Section: Crys and Bilin-based Photoreceptors In Induction Of Photoprotective Mechanisms Insupporting
confidence: 90%
See 4 more Smart Citations
“…Indeed, we observed that LHCSR3 was still induced by blue light (Supplementary Figure 5) and UV-B radiation (Figure 6) in the cia5 mutant, although both the basal and induced levels of expression were lower than in WT cells (but similar fold-change). The lower LHCSR3 mRNA levels present in dark-acclimated cia5 mutant cells are in line with the work by Ruiz-Sola et al (2021) that demonstrates that CIA5-dependent LHCSR3 induction also occurred in total darkness when the availability of inorganic carbon becomes very low (Figure 6B).…”
Section: Crys and Bilin-based Photoreceptors In Induction Of Photoprotective Mechanisms Insupporting
confidence: 90%
“…We measured LHCSR3.1 transcript levels before and after transferring WT and cia5 cells to HSM and we could see that this transfer led to LHCSR3.1 mRNA accumulation (Figure 6B). This result can be explained based on the recent findings of Ruiz-Sola and collaborators who demonstrated that changes in CO2 availability can activate LHCSR3 gene expression even in the absence of light in a CIA5-dependent manner (Ruiz-Sola et al, 2021). In our case the transfer of the cells from TAP to HSM would drop CO2 levels in the culture [CO2 that accumulated in TAP medium (associated with metabolism of acetate) in the dark would decline] and therefore activate LHCSR3.…”
Section: Light Intensity and Co2 Levels Independently Impact Accumulation Of Transcripts From The Photoprotective Genessupporting
confidence: 51%
See 3 more Smart Citations